Cardiorespiratory responses during passive walking-like exercise in quadriplegics - Higuchi, Y; Kitamura, S; Kawashima, N; Nakazawa, K; Iwaya, T; Yamasaki, M (Spinal cord, 2006)
Study design: Cross-sectional and comparative investigation using quadriplegics (QP) and nondisabled subjects (ND). Objective: To evaluate cardiorespiratory responses during passive walking-like exercise (PWE) in QP. Setting: National Rehabilitation Center for Persons with Disabilities in Japan. Method: The subjects were seven male QP with complete lesion (age: 27.0±5.4, injured level: C6–C7) and six male ND (age: 26.3±4.5). Cardiorespiratory responses were measured until voluntary fatigue during PWE, the rhythmical activity of paralyzed lower limbs synchronized with arm movements. Results: There were no significant differences in oxygen consumption (V̇O 2 ), pulmonary ventilation (V̇E), heart rate (HR) and oxygen pulse (O 2 pulse) between QP and ND during PWE. ND showed increased ventilatory equivalent for oxygen (V̇E/V̇O 2 ratio) during exercise, while QP showed a significantly greater respiratory rate (RR) during exercise than ND ( P <0.05). Conclusion: PWE elicited an increase in V̇O 2 with workload increment in QP similar to ND. However, higher RR suggested the intrinsic dysfunction of RR control during submaximal exercise in QP. From these results, it was thought that respiratory response would be the restriction factor of efficient oxygen transportation during PWE in QP.